Extending lithium-ion battery testing capabilities with custom discharge profiles - Toh, Keith Wei Heng (Nanyang Technological University, 2025)
Lithium-ion batteries are a fundamental component in modern technology, powering devices from smartphones to electric vehicles. As their applications continue to grow, understanding their behav- ior under various charge and discharge conditions becomes increas- ingly important. Traditional battery testing methods often rely on fixed charging protocols, but there is a growing need for more flexible and dynamic testing systems. This project focuses on enhancing an existing .NET Framework 4.8 application that executes charge and discharge strategies on lithium-ion batteries. The enhancement intro- duces the ability to utilize custom discharge profiles provided in CSV format, enabling more precise control over battery discharge charac- teristics. By adjusting the applied current at specific time steps, the system facilitates more accurate and reproducible testing. The re- sults of the implementation demonstrate consistent execution across multiple cycles, validating the system’s capability for precise battery testing and opening avenues for further experimentation and analysis.